CURRICULUM ANALYSIS TEACHER PROFESSIONAL EDUCATION PROGRAM (PPG) OF ISLAMIC EDUCATION IN INDONESIA - Fauzan, Fauzan; Bahrissalim, Bahrissalim (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract The existence of Professional Teacher Education program (PPG) becomes a demand after the Law of Teachers and Lecturers (UU G-D) requires professional teachers to have an educator certificates. Professional education contains practical activities of applying academic educational ability in professional activities of teachers in schools along with systematic supervision mechanisms and in a relatively adequate time (at least one year or two semesters). The substance of the Teacher Professional program curriculum rests on the accommodation of teachers' competence, pedagogic, professional, personal, and social. The demands of the teacher's competence spawned several offers of learning expenses that became a person's reinforcement to become a professional teacher, whether related to the content of teaching materials or the strengthening of teaching skills. The structure of the PPG program curriculum contains workshops on learning tool development, teaching exercises through micro teaching- learning, peer learning, and field experience programs (PPL), and pedagogy enrichment programs. Abstrak Keberadaan Program Profesi Guru (PPG) menjadi tuntutan setelah UU G-D mempersyaratkan guru profesional memiliki sertifikat pendidik. Pendidikan profesi berisi kegiatan praktik menerapkan kemampuan akademik kependidikan dalam kegiatan profesional guru di sekolah disertai mekanisme pembimbingan dan supervisi yang sistematis dan dalam waktu yang relatif memadai (sekurang-kurangnya satu tahun atau dua semester). Substansi kurikulum Program Profesi Guru (PPG) bersandar pada akomodasi tuntutan kompetensi guru, yakni pedagogik, professional, personal, dan sosial. Tuntutan kompetensi guru tersebut melahirkan beberapa tawaran beban belajar yang menjadi penguat seseorang menjadi guru professional, apakah terkait dengan konten materi ajar atau penguatan teaching skill. Struktur kurikulum program PPG berisi lokakarya pengembangan perangkat pembelajaran, latihan mengajar melalui pembelajaran mikro, pembelajaran pada teman sejawat, dan program pengalaman lapangan (PPL), dan program pengayaan bidang studi dan/atau pedagogi. How to Cite : Fauzan., Bahrissalim. (2017). Curriculum Analysis Teacher Professional Education Program (PPG) of Islamic Education in Indonesia. TARBIYA: Journal of Education in Muslim Society, 4(2), 148-161. doi:10.15408/tjems.v4i2.6400. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.6400